Analysis of conventional and digital (digora) radiographic methods for - Canova, Giovana C.; de Oliveira, Rodrigo C.; Carneiro, Everdan; da Silva, Renato M.; Brunini, Sérgio H. S.; Letra, Ariadne M. G.; Tavano, Orivaldo; Bramante, Clovis M.; Pereira, José C.; Granjeiro, José M. (Brazilian Dental Science, 2010)
The purpose of this study was to test the hypothesis that the digital radiographic method (Digora), when comparedto the conventional radiographic method, allows better identification of the mineralized tissue barrier formedafter pulpotomy in dogs and protection of the remaining pulp with a resorbable membrane of demineralizedbovine cortical bone (Group I) and calcium hydroxide (Group II). Two dogs were used, according to the InternationalOrganization for Standardization, specification #7405:1997: one for a follow-up period of 7 days andanother for the 70–day period. Ten teeth of each dog were submitted to pulpotomy, being 7 for Group I and 3 forGroup II, resulting in sixteen treated roots for each period. Standardized procedures were used to obtain andanalyze the conventional and digital radiographs. Radiographic images suggesting a mineralized barrier wereonly distinguished in the roots treated with calcium hydroxide; however, no agreement was achieved betweenfour experienced observers. Concerning the comparison between the digital and conventional methods, a suggestiveimage of a mineralized barrier was observed in four and five roots, respectively, but only one such rootbelonged to the follow-up period of 70 days, when a dentin-like bridge was expected. In conclusion, the initialhypothesis was not confirmed.